1998
DOI: 10.1021/jp980181f
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle Neutron-Scattering and Viscosity Studies of CTAB/NaSal Viscoelastic Micellar Solutions

Abstract: Micellar solutions of cationic surfactant cetyltrimethylammonium bromide (CTAB) in the presence of sodium salicylate (NaSal) show a viscoelastic behavior. Small-angle neutron-scattering (SANS) and viscosity studies from CTAB/NaSal micellar solutions are reported. Zero-shear viscosity of these solutions as a function of NaSal concentration (C s ), at all the four measured surfactant concentrations (C d ) of 12.5. 25, 50 and 100 mM, show a double-peak behavior. The effect of C s /C d on two viscosity maxima and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
152
3
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(176 citation statements)
references
References 32 publications
19
152
3
2
Order By: Relevance
“…In contrast, with R 4 N salts the viscosity increased (part I), decreased (part II), and increased again (part III). This behavior is new but akin to that observed with Na salts of organic acids (26,27), which have an altogether different origin (28). With KBr, the continuous viscosity increase may be due to the synergistic effect of Br − and C 7 NH 2 (as discussed in the previous paragraph).…”
Section: Resultsmentioning
confidence: 53%
“…In contrast, with R 4 N salts the viscosity increased (part I), decreased (part II), and increased again (part III). This behavior is new but akin to that observed with Na salts of organic acids (26,27), which have an altogether different origin (28). With KBr, the continuous viscosity increase may be due to the synergistic effect of Br − and C 7 NH 2 (as discussed in the previous paragraph).…”
Section: Resultsmentioning
confidence: 53%
“…A further increase in the concentration above the CMC values resulted in greater selectivity of the Diels-Alder adduct towards the endo product. This might be due to a change in the shape of the micelles when the concentration of the surfactant is increased well above its CMC [33] which favoured the kinetic endo product over the thermodynamic one. However, at this particular concentration, a drop in the yield of the product was observed which might be explained by the change in the micellar structure which rendered the reaction unfavorable.…”
Section: Resultsmentioning
confidence: 99%
“…Required amounts of antioxidants were weighed into 30 ml vials and added to 20 3 methyl gallate (MG) R = C 2 H 5 ethyl gallate (EG) R = C 3 H 7 propyl gallate (PG) R = C 4 H 9 butyl gallate (BG) R = C 8 H 17 octyl gallate (OG) or to 5 ml of D 2 O acetic buffer solution with equivalent surfactant concentrations. Samples needed to be heated to 60…”
Section: Viscositymentioning
confidence: 99%
“…Various studies using a variety of techniques such as rheological approaches, [7][8][9][10][11][12] birefringence, 8 NMR, 4,5,8,13,14 heat capacity, 15 acidity, 13 neutron reflectivity, 6 surface tension, 16 and SANS measurements 4,17,18 have been performed on the influence of organic counterions on cationic surfactants. It has been demonstrated that aromatic counterions are more effective at lower concentrations than salts or electrolytes in inducing the micellar growth, 6,13,19 which can be attributed to interactions with the aromatic π-electron system.…”
Section: Introductionmentioning
confidence: 99%